Black swans, white swans, and 50 shades of grey: Remembering the lessons learned from catastrophic process safety incidents. Issue 2 (6th November 2013) - Murphy, John F.; Conner, James
<x xml:space="preserve">Abstract</x> Last year at the 8th Global Congress for Process Safety, we presented a paper entitled, "Beware of the Black Swan: The Limitations of Risk Analysis for Predicting the Extreme Impact of Rare Process Safety Incidents." The paper discussed the difficulties of predicting black swan events—rare but catastrophic occurrences which continue to happen in the chemical processing industries despite the focus that has been brought to process safety over the past 30–40 years. Once black swan events occur, after investigations and development of lessons learned, they become white swans. By white swans, we mean these type of events become more predictable and as we do hazard identification and risk analysis we become cognizant of the similar potential scenarios in new plants and plant modifications—at least for a while. This article discusses how white swans slowly become greyer as time goes on if the lessons learned from black swan events are not kept fresh. Examples of black swans that become white swans and then become grey as time goes on will be discussed. Ideas of how to keep the white swans from becoming grey with time, including the key role of Management, will also be discussed. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 110–114, 2014